Effects of Flue Gas Desulfurization Gypsum on Crop Yield and Soil Properties in Kansas - DeAnn Presley (Kansas Agricultural Experiment Station Research Reports, 2016)
Flue gas desulfurization (FGD) gypsum was recently approved for use in Kansas as a sulfur (S) fertilizer and as a soil amendment. Gypsum has been known as an effective product used in remediation of sodic soils, as the calcium (Ca) can exchange with sodium (Na) on the cations on clay particles. Marketing efforts have promoted the use of FGD gypsum on non-sodic soils as a means of improving soil health. Two 3-year study sites were established in Kansas in 2013, and no yield effects were observed for any of the site years. Treatment differences for grain quality and soil chemical properties had consistently greater sulfate-sulfur (SO4-S) with increasing FGD application rates. Soil electrical conductivity (EC) had instances where it was greater with increasing gypsum rates. There were no treatment differences for the selected soil physical and biological parameters. During this project, FGD gypsum did not cause changes in soil health at the two sites.
Keywords: gypsum; soil; soil health; soil management; corn; soybean